Altered immune surveillance of B and T cells in patients with persistent residual lung abnormalities 12 months after severe COVID-19 - Julio Flores-Gonzalez; Ivette Buendia-Roldan; Fernanda Téllez-Quijada; Carlos Peña-Bates; Lucero A. Ramón-Luing; Armando Castorena-Maldonado; Ramcés Falfán-Valencia; Gloria Pérez-Rubio; Moisés Selman; Leslie Chavez-Galan; Leslie Chávez-Galán (Respiratory Research)
Abstract Background Post-COVID-19 respiratory sequelae often involve lung damage, which is called residual lung abnormalities, and potentially lead to chronic respiratory issues. The adaptive immune response, involving T-cells and B-cells, plays a critical role in pathogen control, inflammation, and tissue repair. However, the link between immune dysregulation and the development of residual lung abnormalities remains unclear. Methods 109 patients discharged with residual lung abnormalities after a critical COVID-19 were followed for 12 months and divided as full recovery patients (FRG, n = 88) and persistent lung abnormalities (PLAG, n = 21). Cell profiling analysis was done using flow cytometry at 24 h of not antigen-specific in vitro stimulation. Plasma or supernatant levels of IFN-g, IL-4, IL-10, IgM, and IgG were assessed, and 10 patients (5 FRG, 5 PLAG) were randomly selected for detailed immune cell phenotyping and functional analysis of peripheral blood mononuclear cells using flow cytometry. Results Compared to the FRG group, PLAG exhibited an increase of unswitched (p = 0.0159) and decreased double-negative activated B-cells (p = 0.0317), systemic IL-10 levels were lower, displayed reduced frequency of total B-cells, and impaired spontaneous IgM (p = 0.0357) and IgG (p = 0.0079) release in culture. Regarding T-cells, PLAG patients showed a reduction in effector memory CD4 + cells (p = 0.0159) and an increase in CD4 + TEMRA cells (p = 0.0079) following in vitro stimulation. Notably, the PLAG group also exhibited higher frequencies of central memory CD4 + Th2 (GATA3+) T-cells in response to activation than the FRG group (p = 0.0079). Conclusions Patients with residual lung abnormalities 12 months post-critical COVID-19 exhibit impaired B-cell function, increased unswitched B-cells, and higher frequencies of CD4 + TEMRA T-cells following in vitro activation. These immune imbalances may contribute to ongoing lung dysfunction and warrant further investigation as a potential mechanism in residual lung abnormalities. Larger studies are necessary to confirm these findings.